(untitled) (Medico Legal Update, 2019)
The purpose of this study was to develop kinder teacher treatment play therapy for kindergarten children. SPSS version 22.0 for Windows was used for data analysis to develop kinder teacher treatment play therapy for kindergarten children. Among nonparametric statistical methods, the Mann-Whitney U Test and the Wilcoxon Singed-Rank Test were conducted. The results of this study are summarized as follows. Kinder therapy had a positive effect on the improvement of teachers’ interaction. The difference between the pretest and the posttest showed that their positive and permissive interactions improved and that their punitive and detached interactions decreased. This study shows that it is difficult to generalize the result by participation by a small number of people, but it is proved that kinder therapy is effective in improving teacher interaction ability and reducing kinder’s problem behavior in a childcare center.